Fontes alternativas de proteína na dieta de ovinos em confinamento: valor nutritivo e desempenho bioeconômico - Andrade, Igo Renan Albuquerque de (2011)
To verify the bioeconomic performance and physiological adaptability of sheep fed diets containing alternative protein sources in the concentrate as a replacement for soybean meal, this study was conducted. Were used three different alternative protein sources in concentrate in replacement of soybean meal: Leucaena leucocephala leaflet hay (HLL), urea (replacing both 100% of soybean meal) and cottonseed cake, replacing in 51.8% (on a dry matter basis). Was evaluated the finale weight (kg), the total weight gain, average daily gain and the number of days for the lamb gain 12 kg. For a detailed assessment of body development of sheep, weekly morphometric measurements were made in animals, in different parts of the body, as thoracic perimeter, back height, height of the croup, body length, length of the croup and body condition score. The behavioral assessment was conducted instantaneously at intervals of ten minutes (feed intake, rumination, other activities, leisure awake or sleeping, during 24 hours). Besides this, in the interval between two observations, was accompanied the frequency of defecation, urination and water intake. For the analysis of variables bioclimatology, during the experimental period were collected each hour, in the range of 7 a.m until 7 p.m, ambient temperature and relative humidity, using data logger. The natural matter intake of the lot (NMI) was calculated as the difference between the provided and collected the remains the next day for each bay, the dry matter intake (DMI) was obtained multiplying the NMI by their dry matter of feed. The surface temperature of the coat of lambs was collected in two days of the week, in the morning (07:30 a.m) and afternoon (02:00 p.m), with the aid of an infrared thermometer. The economic analyses of the different systems were conducted based on simulations using a number of two hundred animals per batch. When analyzing the finale weight (kg), can verify that the lambs that were fed with the ration which used cottonseed cake in partial replacement to soybean meal (51.8% of dry matter) were who obtained a higher finale weight, total weight gain and average daily gain, combined with a smaller number of days to gain total of 12 kg. Regarding the morphometric measurements, the lambs fed with the diet which used cottonseed cake obtained the best measures both the thoracic perimeter as body condition score. With regard to animal behavior, when looking at continuous variables in % of total days, can observe the variables ingesting food and leisure sleeping, that there was no difference (P>0.05) between different alternative protein sources analyzed, however there was a difference (P<0.05) in other variables between different protein sources. Regarding to punctual activities, can be verified difference (P<0.05) between different protein sources analyzed, in the activities urinating and defecating, and the higher frequency observed in lambs fed with soybean meal and hay of the leaflet of Leucaena for their respective activities. The NMI and DMI were directly influenced by temperature and relative humidity in the morning, and relative humidity in the afternoon and the day. Water consumption was influenced by temperatures in the morning, the critical period, in the afternoon and the daily temperature, as well as the relative humidity of critical period, of the afternoon and the daily relative humidity. Regarding the coat surface temperature, they were influenced directly for all climatic variables analyzed. Rectal temperature was influenced only by temperature and relative humidity in the measurement period. The temperature of the scrotum was not influenced by climatic variables. Regarding to economic indicators, the profit activity in R$/kg PV was higher in the confinement that used cottonseed meal showed as protein source in the concentrate (R$ 0.76/kg PV), followed by those who used soybean meal (R$ 0.64/kg PV), urea (R$ 0.33/kg PV) and hay of leaves of leucaena (R$ 0.21/kg PV). According to the different economic analysis and of investments conducted, can conclude that the cottonseed meal replacing soybean meal in 51.8% was the production system which was more attractive, it allows a greater swing of the selling price of kilograms of live weight of lamb compared to other protein sources studied, which allows the producer to suit a greater elasticity of sales price this product in the market without causing damages to producer.